PENGUJIAN MORTAR MUTU TINGGI SEBAGAI BAHAN PERKUATAN BETON - Amir, Fatmawati (MEKTEK, 2010)
masonry, and etc. In general, mortar made with low strength, between 3-17 MPa and for high strength mortar needed more cement, where are they had relation of compressive strength and water absorption in the mortar. The relation of compressive strength, water absorption and weight density of mortar caused of water cement ratio, and the summed of cement and sand in mortar mixed. Objective of this research was to know the fit of propert high strength mortar for concrete strengthening, where mortar had well workability and more supplied in Indonesia. Compressive strength test used cilindric specimen for concrete and mortar measured 300 mm in hight with 150 mm diameter. Pull out test for concrete used specimen like to the compressive strength test, pull out test for mortar made from cubicus specimen measured 150 mm x 150 mm x 150 mm. All specimen was tested to produce the compressive strenght and pull-out of steel in mortar and concrete. The result show that mortar as well as used for concrete strengthening. Where the compressive strength of mortar was 56,125 MPa highly from concrete as 196,83%. In pull-out test of steel for the two material had same value, therefor mortar was fit to added for concrete strengthening